GENERALIZATION OF THE HUA LO-KEN FORMULA IN THE MATRIX POLYHEDRON (American Journal of Research in Humanities and Social Sciences, 2023)
Integral formulas generalizing the Cauchy integral formula in the theory of functions of one complex variable serve as an important constructive tool. Local residues of many complex variables and integral formulas in multivariate complex analysis serve as a basis in the problems of connecting the values of a function within a domain with the boundary of the domain or with a part of the boundary. Therefore, the study of integral formulas and residues of many variables in function theory plays an important role and is considered one of the topical trends in modern mathematics.